Cloud Computing: Issues and Existing Solutions - Mayur Patil; Rutuja Parkale; Soham Deshpande; Suraj Bhogulkar (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
The computational universe has grown in size and complexity. The cloud is a new technology in the Information Technology (IT) industry that provides IT resources over the internet. Cloud-based services are available on demand, scalable, device agnostic, and dependable. Virtualization is the foundation of cloud computing. Due to cost, virtualization, elasticity, broad network access, metered service features cloud computing becomes integral part of almost all small to medium to large businesses. Cloud services providers and cloud users experiences several key issues of cloud computing such as vendor lock-in, security, incast, scalability, availability, load balancing, performance, data lock-in and many more. In this paper, authors have reviewed security, incast, load balancing, scalability issues of cloud computing. Furthermore, solutions to security, incast, load balancing and scalability issues are analyzed comprehensively.